Recognising, quantifying and accounting for classification uncertainty in type 2 diabetes subtypes - Mori, Tim; Zaharia, Oana P.; Straßburger, Klaus; Dennis, John M.; Mai, Knut; Kabisch, Stefan; Bornstein, Stefan; Szendrödi, Julia; Blüher, Matthias; Meyhöfer, Svenja; Seissler, Jochen; Birkenfeld, Andreas; et al. (Diabetologia, 2025)
Despite continued interest in precision diagnostics and type 2 diabetes subtypes, the challenge of uncertainty in the classification of individuals into subtypes remains. This study introduces a novel method for quantifying and accounting for classification uncertainty in type 2 diabetes subtypes.
Gesehen am 16.12.2025